The Analysis of Entrepreneurial Intention at Undergraduate Students of Universitas Syiah Kuala during the COVID–19 Pandemic: Entrepreneurial Capital Building - Ade Irma Suryani; Megawati Megawati (Universitas Muhammadiyah Yogyakarta, 2022)
Research aims: This study aims to measure the effect of social capital and entrepreneurial attitude orientation towards entrepreneurial intention mediated by psychological capital.Design/Methodology/Approach: A total of 250 out of 25,899 students of Universitas Syiah Kuala were involved in this study. The sample was selected using proportionate stratified sampling. The data were collected through questionnaires. This study employed structural equation modeling to analyze the influence of the variables involved.Research findings: The study uncovered that psychological capital did not play any essential role in the relationship between social capital and entrepreneurial attitude orientation towards the entrepreneurial intention of Universitas Syiah Kuala students.Theoretical contribution/Originality: This study examined the influence of social capital and entrepreneurial attitude orientation towards entrepreneurial intentions mediated by psychological capital during the COVID-19 pandemic. Furthermore, there was not much literature devoted to the topic.Practitioner/Policy implication: This study provides managerial insight and knowledge about social capital and entrepreneurial attitudes orientation towards entrepreneurial intention mediated by psychological capital on Universitas Syiah Kuala students during the COVID-19 pandemic.Research limitation/Implication: Since this study only focused on the entrepreneurial intention of Universitas Syiah Kuala students, the results could not be generalized to the broader phenomenon. In addition, this study only used endogenous variables (social capital and entrepreneurial attitude orientation) and one mediating variable (psychological capital) to analyze the impact of the entrepreneurial intention of Universitas Syiah Kuala students during the COVID-19 pandemic.